Clazakizumab for desensitization in highly sensitized patients awaiting transplantation. Issue 4 (30th December 2021) - Vo, Ashley A.; Huang, Edmund; Ammerman, Noriko; Toyoda, Mieko; Ge, Shili; Haas, Mark; Zhang, Xiaohai; Peng, Alice; Najjar, Reiad; Williamson, Summer; Myers, Catherine; Sethi, Supreet; et al.
Abstract : Alloantibodies are a significant barrier to successful transplantation. While desensitization has emerged, efficacy is limited. Interleukin‐6 (IL‐6) is an important mediator of inflammation and immune cell activation. Persistent IL‐6 production increases the risk for alloantibody production. Here we report our experience with clazakizumab (anti‐IL‐6) for desensitization of highly HLA‐sensitized patients (HS). From March 2018 to September 2020, 20 HS patients were enrolled in an open label pilot study to assess safety and limited efficacy of clazakizumab desensitization. Patients received PLEX, IVIg, and clazakizumab 25 mg monthly X6. If transplanted, graft function, pathology, HLA antibodies and regulatory immune cells were monitored. Transplanted patients received standard immunosuppression and clazakizumab 25 mg monthly posttransplant. Clazakizumab was well tolerated and associated with significant reductions in class I and class II antibodies allowing 18 of 20 patients to receive transplants with no DSA rebound in most. Significant increases in Treg and Breg cells were seen posttransplant. Antibody‐mediated rejection occurred in three patients. The mean estimated glomerular filtration rate at 12 months was 58 ± 29 ml/min/1.73 m 2 . Clazakizumab was generally safe and associated with significant reductions in HLA alloantibodies and high transplant rates for highly‐sensitized patients. However, confirmation of efficacy for desensitization requires assessment in randomized controlled trials. Abstract : Clazakizumab (anti‐IL‐6) for desensitization of highly HLA‐sensitized patients is associated with significant reductions in class I and class II antibodies allowing 18 of 20 patients to receive transplants with no DSA rebound in most.